دور الخدمات الارشادية لمستشار التوجيه في مساعدة التلميذ في بناء مشروعه الشخصي من وجهة نظر تلاميذ سنة اولى ثانوي جذع مشترك ادبي وعلمي ببعض المؤسسات الثانوية بالاغواط - امينة حماد; نسرين حميدات; عون علي (My University, 2023)
The current study aimed at revealing the role of extension services in helping the student to build his personal project from the point of view of firstyears tudents, a common literary and scientific core in some institutions located in the state of Laghouat. It also sought to know the role of extension services in some inter mediate variables such as gender and specialization in help in gthem to build their personal project. Where this study was applied to a sample of 39 male and female students of differents pecializations in the secondary stage, who are practicing their studies in two secondary schools in the state of Laghouat for the academicyear 2032/2022, theywerechosenrandomly. The study approach wasre presented in the descriptive approach in itsanalytical and comparative style. To achieve the objectives of the study, a questionnaire was used that included 26 phrases distributed over four axes. The questionnaire was applied after it was subjected to validity and reliabili typ rocedures, And after statistic maltreatment through the spss program, wereached the follow ingresults: 1- Extension services have no role in helping the student to buildhis personal project. 2- There are no statistic ally significant differences for the role of extension services in helping the student to build his personal project according to gender (male and female). 3- There are statistic ally significant differences for the role of extension services in helping the student to build his personal project according to specialization (literary and scientific). Keywords: counseling services, personale Project, first year secondary school surdents, Common corê